FACTORES DE COMPETITIVIDAD EN LOS PROCESOS DE GESTIÓN DE CALIDAD EN LA INDUSTRIA MÉDICA EN CIUDAD JUÁREZ CHIHUAHUA - Sanchez, Brenda Leyva; Silva, Francisco Arturo Bribiescas (European Scientific Journal, ESJ, 2014)
The quality management processes are an important factor to achieve the desired success of any enterprise. This article analyzes the processes of quality management in the medical industry in Ciudad Juarez Chihuahua, primarily considering three competitive factors, customer focus, leadership in senior management and supplier relationship. The data source to develop this study was obtained through a questionnaire composed of 5 sections for a total of 28 questions, which were answered in full by managers and directors. From a corporate medical industry in the region, to analyze test data correlation between variables was performed.